Modeling and Simulation for 120-type Brake System of Vehicle Unit - ZHU Yinggu; TAN Shouyun; HU Miao (机车电传动)
Modeling and simulation of brake system based on AMESIM platform were very complex, low running effective and poor real-time ability, which maked the simulation system inappropriate for dynamic simulation of long heavy-hauled freight trains. To deal with these problems, by studying the construction and principle of 120 type distribution valves, this paper proposed a new modeling method based on an equivalent model and some simplifications, which has low computational complexity, high simulation efficiency and accuracy with easy parameter adjustment and model modifying.